Estratégias baseadas em recursos para Instituições de Ensino Superior (IES): o papel dos recursos legais - Macêdo, Marcela Lívia Pessoa Soares (Universidade do Vale do Rio dos Sinos, 2021)
This dissertation has as its theme the Higher Education Institutions - HEIs, especially the case study on the Higher Education Center of Vale do Parnaíba - CESVALE, and aims to contribute to the continuation of this HEI in the current educational market, through the consolidation of strategies based on in the theory of Vision Based on resources, as well as the legal resources described for obtaining competitive advantages, ensuring its continuity. Analyze which are the resource-based strategies that Higher Education Institutions, specifically within CESVALE, adopt as a management tool, to obtain competitive advantages, ensuring their permanence in the educational market in Brazil. Data analysis was performed using the VRIO tool, identifying the possibilities for the consolidation of the identified resources, as well as the strengths and weaknesses arising from this analysis. Based on the analysis of the data, we perceive that at CESVALE the management of human resources moved through the survey of the potential of professionals, the development of skills and the necessary training. Therefore, it is clear that the more interaction that exists between the two theoretical models presented - strategic planning and Vision based on resources - the IES can remain in the Higher Education market in Piaui.
Keywords: Planejamento estratégico; Visão baseada em recursos; IES; VRIO; Recursos legais; Strategic planning; Resource-based view; HEI; VRIO; Legal resources; ACCNPQ::Ciências Sociais Aplicadas::Direito